SISTEM DIAGNOSA KESUBURAN SPERMA DENGAN METODE K-NEAREST NEIGHBOR (K-NN) - Rizal Yepriyanto, Kustanto, Yustina Retno Wahyu Utami (Jurnal Ilmiah SINUS, 2015)
Patterns and lifestyle of people today lead a lot discovered problems or diseases suffered by humans that can damage the health. One of these sperm fertility problems in men who have declined in the last two decades. It was explained that environmental factors and lifestyle may affect sperm quality. Several factors can affect sperm fertility include age, high fever, smoking habits and alcohol consumption. It needs to make an application that can help diagnose early fertility of sperm. The process starts from the search criteria and make the training data by taking the results of the UCI Repository. The next step is the calculation of the K-NN method that gives results in the form of sperm diagnosis. Results of this research is a website application interface, and the results of testing the accuracy of the data K-NN performed with 60 training data and testing the data 20, obtained accuracy value by 85%. Keywords: Fertility Sperm, Diagnosis, K-NN, Website